STUDY ON THE OPERATING CHARACTERISTICS OF UNLOADER OF RECIPROCATING COMPRESSOR STEPLESS CAPACITY REGULATION SYSTEM - ZHENG ZhaoXing; JIANG ZhiNong; WANG Yao; ZHANG JinJie (Jixie qiangdu)
Reciprocating compressor stepless capacity control system in the petrochemical industry are widely used, unloading device as a key component of the system actuator, the action characteristics of the relationship between the quality of the system directly related to the efficiency of the air intake system and compressor valve life. In this paper, ANSYS/Ls-dyna explicit dynamics software is used to simulate the automatic opening process of the intake valve at the rated speed of the compressor. The displacement of the valve is measured by the eddy current displacement sensor. On the basis of this, the operation of the unloader under different oil supply pressure and different ejection time is simulated, the ideal hydraulic ejection force and the ejection phase are determined. It is concluded that the reasonable action of the unloader can effectively relieve the vibration of the valve plate and improve the force of the valve.